'Just the two of us': single-operator interventional left atrial appendage closure—a case report. Issue 3 (13th February 2023) - Hammerstingl, Christoph; Yahya, Mohammed Ali; Völz, Alexander
Abstract: Background: Different procedural strategies have been published targeting to facilitate transcatheter left atrial appendage closure (LAAc). We demonstrate feasibility of a procedural set-up allowing single-operator LAAc in a selected patient. Case summary: A 87-year-old male with persistent Afib (CHA 2 DS 2 VASc, five; HASBLED, three) was referred to our hospital for LAAc. Pre-procedural planning and device sizing with three-dimensional transesophageal echocardiography (3DTEE) confirmed a non-complex anatomy of the essential anatomical structures predicting suitability for LAAc. Therefore, the procedure was performed with a simplified single-operator interventional approach. Intraprocedural TEE guidance, device preparation, and LAAc were accomplished by the interventionalist himself. For procedural guidance, the TEE probe was arranged and handled in a technique comparable to the use of intracardiac echocardiography (ICE). Procedure time (skin-to-skin) was 21 min, left atrial access time 9 min, and fluoroscopy time was 4:28 min without the use of contrast dye. The patient was discharged the following day in good medical conditions. Discussion: To the best of our knowledge, this is the first report on successful single-operator LAAc in a selected patient. The intervention, pre-procedural screening, and intraprocedural 3D TEE were performed by one single experienced interventionalist. This simplified technique is based on a standardized pre-procedural imaging-protocol with 3D echocardiography. According to our experience, this streamlined approach is a valuable option in non-complex LAAc cases. In the growing field of structural cardiac interventions, this approach might be an interesting option for centres with limited personal and technical resources.